2009
DOI: 10.4161/cbt.8.5.7687
|View full text |Cite
|
Sign up to set email alerts
|

Combined endostatin and TRAIL gene transfer suppresses human hepatocellular carcinoma growth and angiogenesis in nude mice

Abstract: Endostatin can inhibit tumor growth by blocking angiogenesis, whereas tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) may function as a soluble cytokine to selectively kill cancer cells without toxicity to most normal cells. To establish the combined anti-tumor therapeutic effect of endostatin and soluble TRAIL (sTRAIL), we performed intra-tumoral human endostatin and sTRAIL gene transfer using plasmid pVAX1 as a vector in a nude mouse model of human liver cancer. For subcutaneously inoculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The key point of gene therapy is to establish an effective gene delivering system. Our data indicate that the combination gene therapy of adenovirus-mediated TRAIL with endostatin exhibits significant antitumor activities through induction of apoptosis and inhibition of angiogenesis, compared with single Ad-T or Ad-E. Our results are in agreement with the previous study by Zhang et al (20), in which sTRAIL and endostatin genes were transferred using plasmid pVAX1 as a vector. By contrast, the Adeno-X expression system was utilized in our study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The key point of gene therapy is to establish an effective gene delivering system. Our data indicate that the combination gene therapy of adenovirus-mediated TRAIL with endostatin exhibits significant antitumor activities through induction of apoptosis and inhibition of angiogenesis, compared with single Ad-T or Ad-E. Our results are in agreement with the previous study by Zhang et al (20), in which sTRAIL and endostatin genes were transferred using plasmid pVAX1 as a vector. By contrast, the Adeno-X expression system was utilized in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Previous evidence has shown that carcinoma growth and angiogenesis were suppressed by combined plasmid-mediated endostatin and TRAIL gene therapy in mice (20). The current study reports on the use of an adenovirus as the gene delivery vector to construct the recombinant adenovirus Adeno-X-TRAIL (Ad-T) and Adeno-X-endostatin (Ad-E) and to examine whether the combination of TRAIL with endostatin works synergistically against HCC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, endostatin is an inhibitor of angiogenesis encoded by the COL18A1 gene on HSA21. Endostatin gene therapy in combination with other genes (e.g., interferon gamma, TRAIL) or in combination with drug therapies (e.g., Cisplatin) apparently suppresses breast, lung, and colon cancer in a mouse model (Bai et al 2009;Liu et al 2009;Zhang et al 2009). Moreover, Minami et al (2004) provided evidence that RCAN1 (DSCR1) might be a tumor suppressor when overexpressed.…”
Section: Ds Hsa21 Genes and Cancermentioning
confidence: 98%
“…Since vasostatin was an anti-angiogenesis agent which doesn't impact on tumor cells, the apoptosis activity of VAS-TRAIL toward tumor cells was equivalent to that of sTRAIL. However, endothelial cells treated with anti-angiogenesis agent may show enhanced sensibility to the extrinsic and intrinsic apoptotic pathways [1,24]. Therefore, VAS-TRAIL showed a synergism on FBHE cells which resulted in higher apoptosis activity than sTRAIL and vasostatin alone.…”
Section: Biological Activity Of the Refolded Vas-trail Proteinmentioning
confidence: 89%